Accessibility-Based Equity of Public Facilities: a Case Study in Xiamen, China - Li, Yongling; Lin, Yanliu; Geertman, Stan; Hooimeijer, Pieter; Xu, WangTu (Ato) (Applied spatial analysis and policy, 2021)
China's rapid economic development has led to inequality in terms of property, education, and health. Equal access to basic public facilities has become a key concern of inclusive development policies. However, previous studies have paid little attention to the effects of different travel modes on the accessibility of basic public facilities. The present research fills this gap. Taking Xiamen city as a case study, it explores the degrees of horizontal and vertical equity by examining the accessibility of various basic public facilities, paying attention to different travel modes and travel times. The results for Xiamen city show that disadvantaged groups experience a greater level of inequity. By taking these aspects into account, one is better equipped to identify areas in the city where access to basic public facilities is in need of substantial improvement.